Structural changes of pelvic/hip entheses and their evolution over time in psoriatic arthritis patients starting bDMARDs - Ayan, Gizem; Sadıç, Abdurrahman; Kılıç, Levent; Kalyoncu, Umut (Acta Medica, 2026)
Objective: This study aimed to investigate the frequency and progression of pelvic and hip entheseal structural changes in PsA patients initiating biologic therapy. Methods: Records from the Hacettepe University Rheumatology Biologic Therapy Registry (HUR-BIO) were retrospectively reviewed. PsA patients with pelvic radiographs obtained within ±1 year of biologic therapy initiation were included. Radiographs were assessed according to the modified New York criteria, and entheseal involvement at the ischium, symphysis pubis, iliac wings and greater/ lesses trochanter was graded from 0 (none) to 4 (florid new bone formation). Grade 2 or higher was considered clinically relevant. Demographic and clincal characteristics were compared between patients with/ without structural changes and progression of these lesions were assessed. Results: A total of 108 patients (68.5% female; mean age 41.5 ± 11.6 years; mean PsA duration 2.2 years) were included. Baseline mNY positivity was detected in 45.4%. Bilateral relevant entheseal involvement was observed in 21.9% at the ischium, 15.3% at the symphysis pubis, and 7.7% at the iliac wings. Greater trochanteric enthesopathy was 2% on the right side. Male patients, with higher BMI and older age with family history tended to have more structural lesions. After a mean follow-up of 38.6 months, data from 48 patients were available. Most progression was limited to a one-grade increase at the ischium (28%). Conclusion: Major pelvic entheseal lesions, predominantly at the ischium and symphysis pubis, are relatively common in PsA but show minimal radiographic progression under biologic therapy.